Impacts of nanomaterials on bacterial quorum sensing: differential effects on different signals. Issue 2 (22nd February 2016) - Mohanty, Anee; Tan, Chuan Hao; Cao, Bin
Abstract : We report for the first time that different QS signals may respond differently to nanomaterials, which may result in a complex influence of nanomaterials on the overall structure and function of the whole community. Abstract : Using Pseudomonas syringae and Pantoea stewartii as model organisms, we quantified the influence of silver nanoparticles and single-wall carbon nanotubes on the production of different acylated homoserine lactones for quorum sensing (QS). This study reports for the first time on differential effects exhibited by nanomaterials on different QS signals.